A Confucian Account of Contemplation-in-Action (The Macau Ricci Institute Journal, 2020)
Philosophically speaking, “to contemplate” is to think deeply about an issue or to consider something at length. “Contemplation” in the Aristotelian tradition is understood to involve an elevated intellectual state and it leads a human being to the activity of happiness. The object of contemplation can refer to the nature of the good or even the virtues. The outline and objectives of Confucian contemplative practice can be found in the classical Chinese text Zhongyong (Central and Constant). The purpose of Confucian spirituality is to become a junzi (noble person) and this is achieved by the practice of shendu (being careful about one’s inner self). Gao Panlong’s reflections on jingzuo (quiet-sitting) serve as the theoretical basis for showing how Confucian contemplative practice promotes moral excellence in the ordinary affairs of professional life. A comparative approach is employed in this paper in order to use the conceptual framework from the Nicomachean Ethics to re-construct an account of contemplation-in-action as found in the Zhongyong and the Jingzuoshuo (Treatise on Quiet-Sitting). Specifically, it is argued that the Aristotelian notions of “contemplation” and “action” are analogous to the corresponding Confucian concepts of jing (stillness) and dong (movement).